Base of tongue schwannoma on a 22 year old lady: a rare case - Indrasari, Sagung Rai; Fedriani, Jessica (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Schwannomas are benign tumours arising from the Schwann cells. Around 25-45% schwannomas have been reported occured in head and neck region, but only 1% located intraoral. We report a case of 22 year old woman who presented with foreign body sensation in throat, dysphagia, change of voice, and snoring. There was a slowly growing, solitary, encapsulated, painless, mass on the tongue base. Microscopically, it had the typical features of schwannoma, the diagnosis being supported by a strong positivity for S-100 protein. Ki67 staining showed low proliferative index (<5%) indicated benign schwannoma. CT-scan of oropharynx demonstrated a well-circumscribed soft tissue density mass, oval shape, connected with the left portion base of tongue, homogenous, and strong enhancement mass. The entire mass was removed in general anesthesia with conservative surgical excision via trans-oral route, histopathologic reported consistent as schwannoma. The patient remained disease-free, without any residual problems. Although the rarity of schwannoma on the tongue base, this case highlights the importance of including it in the differential diagnosis of mass from the tongue base. To the best of our knowledge, our case is only the twentieth of schwannoma at the base of tongue that reported in the literature.